Investigation of Intestinal Schistosomiasis among School Children in Nteje Town, Oyi Local Government Area of Anambra State - C Lucy , Anyaegbunam; ryblessing , Ilodiuba Ma C. (African Journal of Education,Science and Technology (AJEST), 2016)
Intestinal parasitic infections are important public health challenges among underprivileged communities. An investigation of Intestinal Schistosomiasis was carried out in Nteje, Oyi Local Government Area of Anambra State between June and September 2014. Structured questionnaires based on knowledge, attitude and practices (KAP) was used to elicit information from 200 school children in 10 schools in the town. 34(17%) had knowledge of intestinal Schistosomiasis, 123(61.5%) collect water regularly from the water bodies and 107(53.5%) swim frequently in the water bodies. 200 stool samples were examined considering the physical appearance and by wt mount using physiological saline on slides and examined under the light microscope. 20(10.0%) were positive for the infection. In age related infection, 10-14 age group had the highest infection of 5.0% while in the infection according to sex, males had 8.0% prevalence and females 2.0%. In the infection intensity, 14(7.0%) had light infection and 6(3.0%) had moderate infection. The exposure of the school children to intestinal schistosomiasis in the study area can be attributed to low socio-economic status, poor environmental sanitation, poor parental care and ignorance. This parasitic infection will continue to be a threat to health if appropriate actions are not taken to check its transmission.